Understanding the visible-light-initiated manganese-catalyzed synthesis of quinolines and naphthyridines under ambient and aerobic conditions - Patra, Kamaless (2023)
Polyaromatic N-heterocycles are some of the most common building blocks in natural products and active pharmaceutical ingredients. Significant efforts have been devoted to developing catalytic protocols, including those which use an acceptorless dehydrogenation strategy at elevated temperatures, to produce polyaromatic N-heterocycles like quinolines and naphthyridines. However, photoinitiated catalysis driven by visible light offers a milder and often more selective protocol as an alternative to thermal reactions. Here, we present the catalytic syntheses of quinolines and naphthyridines from ortho-aminobenzyl alcohols and ketones using the photocatalyst [Mn(L1H)(CO)3Br] (L1H = 7-hydroxy-2-methyl-1,8-naphthyridine-N-oxide), bearing a phenolic unit on a 1,8-naphthyridine-N-oxide scaffold, under ambient and aerobic conditions with visible light illumination. We describe a broad, functional group-tolerant substrate scope of >30 examples under modest reaction conditions. A variety of 2-aminobenzyl alcohols containing electron-donating and electron-deficient groups and (2-aminopyridin-3-yl)methanol are converted to the corresponding quinolines and naphthyridines using ambient air as an oxidant in the presence of KOH. We synthesized a wide range of derivatives, including some of the bioactive antimalarial drug chloroquine and the steroids progesterone and pregnenolone to highlight the value-added applications of this catalytic protocol for pharmaceutical ingredient and natural product syntheses. We performed substrate viability, ultraviolet-visible, electron paramagnetic resonance, and X-ray photoelectron spectroscopy studies, as well as density functional theory calculations to gain mechanistic insights to the reaction pathway. The catalytic cycle involves condensation of the amino group in the ortho-aminobenzyl alcohol with the ketone initially, which is followed by aerobic oxidation of the benzyl alcohol to the corresponding benzaldehyde catalyzed by the photoinitiator [Mn(L1H)(CO)3Br] in the presence of visible light, and finally, a KOH-promoted condensation and cyclization to afford quinolines as the final products.